2022
DOI: 10.1186/s43058-022-00277-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for the spread of patient-reported outcome (PRO) data collection from primary care to community pharmacy: a mixed-methods study

Abstract: Background Medication non-adherence is a significant public health problem. Patient-reported outcomes (PROs) offer a rich data source to facilitate resolution of medication non-adherence. PatientToc™ is an electronic PRO data collection software originally implemented at primary care practices in California, United States (US). Currently, the use of standardized PRO data collection systems in US community pharmacies is limited. Thus, we are conducting a two-phase evaluation of the spread and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…DHIs targeting HCPs included (but are not limited to) mobile apps targeting patients’ smoking cessation [ 45 ] and medication adherence counseling [ 46 , 47 ], telemedicine and telehealth [ 48 , 49 ], cancer prevention decision support tools [ 50 ], e-consultation between primary care providers and specialty care expertise [ 51 , 52 ], and e-learning for dementia caregiver education [ 53 ]. Two studies targeted health system managers and an information system for case-based surveillance [ 54 ] and a patient-reported outcome data collection system [ 55 ]. Two studies focused on data services including big data analytics [ 56 ], the former being reported in combination with clients, and an electronic patient falls reporting system [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…DHIs targeting HCPs included (but are not limited to) mobile apps targeting patients’ smoking cessation [ 45 ] and medication adherence counseling [ 46 , 47 ], telemedicine and telehealth [ 48 , 49 ], cancer prevention decision support tools [ 50 ], e-consultation between primary care providers and specialty care expertise [ 51 , 52 ], and e-learning for dementia caregiver education [ 53 ]. Two studies targeted health system managers and an information system for case-based surveillance [ 54 ] and a patient-reported outcome data collection system [ 55 ]. Two studies focused on data services including big data analytics [ 56 ], the former being reported in combination with clients, and an electronic patient falls reporting system [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most (7/8) cases included all these steps; three included an additional step of making research design decisions (e.g., choosing the control condition; selecting/refining measures). For the third step of selecting EBI adaptations and/or implementation strategies, all cases selected implementation strategies, while 3 also selected adaptations of the EBI ( 27 , 29 , 34 ).…”
Section: Case Comparisonmentioning
confidence: 99%
“…In fact, EBQI may be a “meta-strategy” during the active implementation phase through which many other strategies can be decided upon and deployed (e.g., working groups, facilitation calls, champion engagement). We believe operationalizing EBQI as an implementation strategy is most fitting when the purpose is “to enhance the adoption, implementation, and sustainability of a clinical program or practice” ( 37 ) or for “creating buy-in among stakeholders.” ( 34 ) The Department of Veterans Affairs (VA) Quality Enhancement Research Initiative (QUERI) implementation road map ( 38 ) conceives of EBQI in this way and illustrates how EBQI operates during both active implementation and sustainment phases. Continuation of EBQI engagement across implementation phases allows continuation of partnerships formed in pre-implementation.…”
Section: Recommendations For Ebqi In the Pre-implementation Phase Ref...mentioning
confidence: 99%